Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Motivasi Belajar, Pemecahan Masalah dan Penguasaan Konsep Matematika SD - Evalin Ndoen; Nancy Susianna (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine differences in learning motivation, problem-solving skills, and concept mastery between grade V students who use the guided inquiry learning model and students who use the lecturing method. This research was a quantitative study using the weak experiment method. The data collection in this study was carried out by rubric and test. Technique of data analysis in this study was descriptive and inferential. By descriptive, the data analysis was carried out by counting the score average and n-gain, while by inferensial the data analysis was carried out in non-parametric method using Mann Whitney test to prove the hypothesis. The results of the learning motivation hypothesis test show asymp. sig (2-tailed) = 0.000, problem solving skills with asymp. sig (2-tailed) = 0.011, and concept mastery with asymp. sig (2-tailed) = 0.002. Based on the findings, it can be concluded that there are differences between the class at SD XYZ Tangerang that employ the guided inquiry learning model and class that employ the lecturing method in terms of learning motivation, problem-solving abilities, and concept mastery.